Synthesis of Highly Selective Submicromolar Microcystin‐Based Inhibitors of Protein Phosphatase (PP)2A over PP1. (10th October 2016) - Fontanillo, Miriam; Zemskov, Ivan; Häfner, Maximilian; Uhrig, Ulrike; Salvi, Francesca; Simon, Bernd; Wittmann, Valentin; Köhn, Maja
Abstract: Research and therapeutic targeting of the phosphoserine/threonine phosphatases PP1 and PP2A is hindered by the lack of selective inhibitors. The microcystin (MC) natural toxins target both phosphatases with equal potency, and their complex synthesis has complicated structure–activity relationship studies in the past. We report herein the synthesis and biochemical evaluation of 11 MC analogues, which was accomplished through an efficient strategy combining solid‐ and solution‐phase approaches. Our approach led to the first MC analogue with submicromolar inhibitory potency that is strongly selective for PP2A over PP1 and does not require the complex lipophilic Adda group. Through mutational and structural analyses, we identified a new key element for binding, as well as reasons for the selectivity. This work gives unprecedented insight into how selectivity between these phosphatases can be achieved with MC analogues.